Geomorphologic Character & Receding Trend of Kolahoi Glacier in Kashmir Himalaya - Hassan, T.A. Kanth, Aijaz Ahmad Shah, Zahoor ul (Recent Research in Science and Technology, 2011)
Glaciers are a valuable source of fresh water which sustain life and provide water for drinking, irrigation, hydro power generation, etc. Besides, these exert considerable influence on the climate of a region and fluctuate in dimension in response to the climatological changes and therefore, these are regarded as sensitive indicators of the climate of a region. Glaciers are in the process of retreat in almost all the parts of the world due to global warming. The same process of retreat is found in the valleyÃ¢â‚¬â„¢s largest glacier, Kolahoi. Thus, it is of great significance to obtain the accurate information of changes in Kolahoi glacier Ã‚Â (34Ã‚Â° 07Ã¢â‚¬Â² to 34Ã‚Â° 12Ã¢â‚¬Â² N latitude; & 75Ã‚Â° 16Ã¢â‚¬Â² to 75Ã‚Â° 23Ã¢â‚¬Â² E longitude, Liddar valley, Kashmir Himalayas). The study was carried out using Remote Sensing and GIS techniques and thorough field observations were conducted to identify the geomorphologic features. The area of the glacier receded from 13.57kmÃ‚Â² in 1963 to 10.69kmÃ‚Â² in 2005, registering a change of 2.88km2at a rate of 0.068km2per year. The Crevasses developed in the ablation portion of the Kolahoi Glacier and the formation of numerous caves at its snout position act as the important indicators of its recession. The result of this retreat will prove disastrous for the valley in many fields like drinking water, agriculture, horticulture, ground water, hydro power capacity of the state, etc. Therefore, we need to make efforts to save this precious source of water for the present as well as for future generations.